Evaluation of major foliar diseases in commercial oil palm nurseries for improving disease management - Muhamad Nor, Azlan Azizi (2014)
Field surveys were conducted in nine selected oil palm nurseries in Peninsular Malaysia including government and private nurseries which provided and supplied oil palm planting materials in Malaysia. Studies covered 4 nurseries in Johor (Kluang, Bkt Tongkat, Kahang and Ayer Hitam), 3 nurseries in Perak (Teluk Intan, Permatang Guntung and Kg Bakar Arang) and 2 nurseries in Selangor (Sepang and Kuala Langat). The disease evaluation revealed that leaf spot disease was a major problem with the highest mean incidence is 62.81% compared to anthracnose disease at 16.52%. For disease incidence of leaf spot disease, the highest incidences were recorded in Kuala Langat, Selangor (90.3%) and Kluang, Johor (87.7%). The least incidences of leaf spot were recorded in 3 nurseries in Perak occurring between 50 to 55%. For assessment of disease incidence of anthracnose, the highest incidence was recorded in Kuala Langat, Selangor (45.0%) and the least incidences were recorded in 6 nurseries which were located in Johor and Perak occurring between 8.0 to 14.0%. For assessment of disease severity, high severities for leaf spot disease were recorded in Kluang (64.7%) and Kahang, Johor (59.22%). Besides, the least severity was recorded in Permatang Guntung, Perak with 19.23%. For severity of anthracnose, high severities were recorded in Kuala Langat, Selangor (9.1%) and Teluk Intan, Perak (6.57%) and the least severities were recorded in 6 nurseries which were located in Johor and Perak occurring between 1.0 to 2.5%. The study also found disease incidence of leaf spot and anthracnose diseases were both highly significant with different age of seedling. As the seedling became older, incidence of leaf spot and anthracnose diseases were reduced. For leaf spot disease, seedling 0-4 month score the highest percentage at 77.47% followed by 4-12 month which was 72.89% and seedling with age 12 month and above were most resistance with lowest score 49.0%. This was similar with disease incidence of anthracnose for 0-4 months (21.56%), 4-12 months (16.86%) and with the least incidence was observed in seedlings aged 12 months and above at 14.89%. For interaction of seedling age with disease severity of leaf spot, study revealed that there was highly significant relationship between disease severity and seedling ages. Seedling with age 0-4 month were most susceptible and severely affected (50.90%) followed by seedling age 4-12 month (39.84%) and the most resistance seedling age is comes to seedling with 12 month and above with only 18.4%. However, for disease severity of anthracnose, there was no significant relationship. Study found that, these three stages of ages which were 0-4 month (3.5%), 4-12 month (3.83%) and 12 month and above (3.31%) score the disease severity with mostly the same with each other. The symptoms of leaf spot and anthracnose diseases also were recorded and characterized based on field observation. For isolation of pathogen, study indicated that anthracnose was found to be associated mainly with Colletotrichum spp. Meanwhile, leaf spot was found mostly associated with Curvularia sp., and Pestalotiopsis sp. For interaction of agricultural practices with disease incidence and severity of leaf spot, study found that there was no significant correlation between disease incidence of leaf spot with irrigation system, frequency of watering, mulching and water sources for seedling 0-4 month and 12 month and above. However, for seedling 4-12 month, there was negative correlation between water sources with leaf spot incidence (-0.76*) and severity (-0.84**). For anthracnose disease, there was no significant correlation between disease incidence and severity with irrigation system, frequency watering, mulching and water sources for seedling 0-4 month, 4-12 month and 12 month and above.